First breeding record of Javan Plover Anarhynchus javanicus (Charadriiformes: Charadriidae) in Flores, East Nusa Tenggara, Indonesia - Crossland, Andrew; Crutchley, Phil (BIO PALEMBANICA, 2025)
The Javan Plover Anarhynchus javanicus is a range-restricted shorebird endemic to the Indonesian archipelago. While long considered resident in Java and nearby islands, its status on the island of Flores has remained poorly understood, with no previously documented breeding records. In March and April 2025, we conducted targeted field surveys in the Labuan Bajo region of western Flores to search for potential breeding activity. Two active nests were located with a minimum population of five territorial pairs at Sawah Kaca Mese, 6 km south of Labuan Bajo. This constitutes the first confirmed evidence of breeding by A. javanicus on Flores. These observations underscore the need for further surveys across Flores to reassess the species’ distribution, population size and breeding status. Keywords: Anarhynchus javanicus, breeding, Javan Plover, Labuan Bajo, Lesser Sunda Islands.